Wolda Award of Excellence - Papadima, Aspasia (My University, 2026)
Wolda Award of Excellence for exemplary design and concept in the category Logo New Europe & Africa 27 logos and identities from 30 countries participated in the fourteenth Wolda – Worldwide Award 2023.
Keywords: Arts and entertainment